Gambaran Pengetahuan Keluarga Tentan Pola Makan Resiko Penyakit Hipertensi di Tanjung Muda Dudun III Kecamatan Air Putih Batu Bara Tahun 2024 - Evi Pani Simarmata; Grytta Tondang; Maga Siringo-Ringo; Amando Sinaga (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Diet is a description or daily eating habits that characterize a person and are important behaviors that can influence a person's nutrition. This is because the food and drinks consumed will affect a person's nutrition. Knowledge also provides understanding to families, especially in caring for family members with hypertension in terms of serving foods that are recommended, those that are avoided and those that are not recommended. As well as daily habits that can trigger increased blood pressure. Aim: To find out the picture of family knowledge about eating patterns, risk of hypertension in Dusun III, Tanjung Muda Village, Air Putih Subdistrict, Batubara Regency, Year. Research Method uses a quantitative design with approaches to empirical studies to collect, analyze and display data in numerical form (numbers), rather than narrative. The sample in the study was 66 families. The sampling technique uses purposive sampling, which is a sample determination technique by selecting samples from the population according to what the researcher desires. Instrument: The instrument used is a questionnaire. The results of the study found that the frequency distribution of family knowledge about the frequency of food for hypertension was that of the 66 respondents, the majority were in the good category, 58 respondents (87.9%) and the minority in the fair category, 8 respondents (12.1%), the distribution of the frequency of eating patterns in the disease. hypertension, that of the 66 respondents, the majority were in the poor category, 35 respondents (53.0%) and the minority in the sufficient category, 8 respondents (12%). Suggestions: The results of this research can be used as a basis for developing further research in expanding the assessments that have been carried out, especially regarding family knowledge about eating patterns.